Deletions of the homeobox gene SHOX (short stature homeobox) are an important cause of growth failure in children with short stature - Rappold, Gudrun; Fukami, Maki; Niesler, Beate; Wöginger, Simone; Zumkeller, Walter; Bettendorf, Markus; Heinrich, Udo; Vlachopapadoupoulou, Elpis; Reinehr, Thomas; Onigata, Kazumichi; Ogata, Tsutomu (The journal of clinical endocrinology & metabolism, 2002)
Short stature, with an incidence of 3 in 100, is a fairly frequent disorder in children. Idiopathic short stature refers to patients who are short due to various unknown reasons. Mutations of a human homeobox gene, SHOX (short stature homeobox), have recently been shown to be associated with the short stature phenotype in patients with Turner syndrome and most patients with Léri-Weill dyschondrosteosis. This study addresses the question of the incidence and type of SHOX mutations in patients with short stature. We analyzed the SHOX gene for intragenic mutations by single strand conformation polymorphism, followed by sequencing, in 750 patients and for complete gene deletions by fluorescence in situ hybridization in 150 patients (total, 900 patients). This is the largest group of patients with short stature studied to date for SHOX mutations. All patients had a normal karyotype, and their height for chronological age were below the third percentile or minus 2 sd of national height standards. All were without obvious skeletal features reminiscent of the Leri-Weill syndrome at the time of diagnosis.Silent, missense, and nonsense mutations and a small deletion in the coding region of SHOX were identified in 9 of the 750 patients analyzed for intragenic mutations. Complete gene deletions were detected in 3 of the 150 patients studied for gene deletions. At least 3 of the 9 intragenic mutations were judged to be functional based upon the genotype- phenotype relationship for the parents and normal control individuals. We conclude that SHOX mutations have been detected in 2.4% of children with short stature. The spectrum of SHOX mutations is biased, with the vast majority leading to complete gene deletions. The prevalence of short stature due to SHOX gene mutations among children with short stature appears to be similar to that of GH deficiency or Turner syndrome. Family studies of the children with SHOX mutations often reveal older family members with same mutation who exhibit mild skeletal features reminiscent of the Turner syndrome, such as high-arched palate, short neck, abnormal auricular development, cubitus valgus, genu valgum, short fourth metacarpals, and Madelung deformity.